Serum KIBRA mRNA and Protein Expression and Cognitive Functions in Depression - Talarowska, Monika (Med Sci Monit, 2016)
BACKGROUND: Genes participating in synaptic signalling or plasticity in brain regions such as the prefrontal cortex (PFC) and the hippocampus have been implicated in cognition. Recently, a new gene (KIBRA, WWC1) has been added to this group due to its impact on memory performance. Recurrent depressive disorder (rDD) is a multifactorial disease, that one of the typical features is cognitive impairment. The main objective of this study was to perform an analysis of the KIBRA gene on both mRNA and protein levels in patients suffering from rDD and to investigate the relationship between KIBRA expression and cognitive performance. MATERIAL/METHODS: The study comprised 236 subjects: patients with rDD (n=131) and healthy subjects (n=105, HS). Cognitive function assessment was based on: Trail Making Test, The Stroop Test, Verbal Fluency Test and Auditory Verbal Learning Test. RESULTS: Both mRNA and protein expression levels of KIBRA gene were significantly higher in healthy subjects when compared to rDD. The presented relationship is clear even after taking age, education and sex of the examined subjects into consideration. No statistically significant relationship was found in the experiments between any of the conducted tests and KIBRA gene expression on mRNA level for both the rDD and HS groups. The presented study has limitations related to the fact that patients were being treated with antidepressant. This is relevant due to the fact that some antidepressants may affect mRNA expression. Number of patients and healthy subjects may result in the lack of statistical significance in some cases. CONCLUSIONS: 1. The results of our study show decreased expression of the KIBRA gene on both mRNA and protein levels in depression. 2. We did not find any significant relationship between KIBRA gene expression and cognitive functions in case of both the healthy subjects and the patients affected by rDD.